Pharmacoepidemiological Study of Self-Medication in Indore City - MS, Rajput; V, Mathur; Satrawala, Yamini; Nair, Veena (Indian Journal of Pharmacy Practice)
Self-medication and non-doctor prescribing of drugs is common in developing countries. The objectives of this research were to explore lay medication activities as an aspect of self-managed health care to identify sociomedical characteristics and to establish the prevalence, attitude knowledge, and sources of information of self-medication in Indore city. A cross-sectional study was conducted to determine the extent and pattern of self-medication. Data were collected from a random sample of 135 pharmacists from various pharmacies in city following WHO methods. The prevalence of self-medication was estimated. Respondents were questioned about the, self-treated symptomatic conditions, recent medication activities, the use of prescribed medicine in self-treated illness episodes, and the use of suitable dosage forms. The prevalence of self-medication in Indore city is high. This study contributes to a growing body of international evidence which has demonstrated that self-medication is a vital part of daily self-care behavior. Patient education and awareness campaigns are necessary to promote the role of the pharmacist in India, particularly because in modern society the pharmacist plays an active role in the provision of drug information. Strict policies need to be implemented on the advertising and selling of medications to prevent this problem from escalating.
Keywords: Self-medication; Pharmacoepidemiology; Indore city